Efektivitas Pembelajaran Daring Terhadap Mata Pelajaran Matematika Pada Siswa SD Kelas IV - Khurin In'Ratnasari (Program Studi PGMI, IAI Al-Falah As-Sunniyyah Kencong, 2020)
Corona pandemic virus disease 2019 ( covid-19 ). conventional has disrupted the learning processThen required analysis of how this pandemic have a direct impact on the outcome of. student learningAlthough online learning can be implemented as a substitute for conventional, is learning but the changes have the direct effect on the outcome which has not known. student learningThe study aimed to identify the effectiveness of online learning during the pandemic and change the overall student learning in one class.This research to discovering whether online learning mathematics work for primary school student.Methods used aadalah qualitative compare in value all students in the first half with the odd in the same lessons, where in the first half of normal 1 learning to be carried out , while in the first half of the even online to be carried out .Data collection technique using interviews and documentation .The interviews and the purpose of comparing the students to study analyzed the results of the quantitative uses the technique .The research results show that of the 38 fourth grade students , about 97 % 37 students has experienced a fall in the value of the end of the semester .An example of this was caused by loss of learning activities face to face between teachers and their students , reduced review teacher supervision in the teaching process long distance learning students at the time , so that the thing is hinder the implementation of explanation and a dialogue between students and teachers.